Strategies For Healthcare Workers Retention In Saudi Arabia: A Narrative Review Through The Lens Of Push-Pull Theory (Journal of Namibian Studies : History Politics Culture, 2019)
This review aims to explore the push and pull factors that influence the retention intentions of healthcare providers in Saudi Arabia with the aim of developing effective retention strategies. The research also aims to make clear the need for original research to investigate these factors in health care in Saudi Arabia. To accomplish these tasks, this review is structured to include four main sections. The first section, which includes the introduction and the current section, represents the beginning of the desired investigation of this study. The section introduces the push-pull theory as a theoretical framework for this review (World English Journal & Alkubaidi, 201). It, then, provides an overview of the healthcare workforce in Saudi Arabia and the burnout and retention issues that exist in this field. Finally, this section establishes the aim of this review.